ANTHROPOLOGY OF IMPERIAL POWER: THE KHAKENTS LANDS AND LAWYER S. LAPIN - Алимджанов, Бахтиёр (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article examines the "Hakent case", which arose after the uprising of Dukchi Ishan in 1898. The well-known lawyer S. Lapin, who defended the interests of the local population before the imperial authorities, took up the case. The article analyzes the reason for the refusal of the imperial authorities not to grant the petition of local residents.